RFID 이용 돈사 출입 자동관리 시스템 개발 - 김혁주(Hyuck-Joo Kim); 전형순(Hyung-Soon Jun); 유병기(ByeongKee Yu) (한국콘텐츠학회 논문지, 20(3), 2020)
As a result of reenforcement of livestock industry licensing and livestock related vehicle registration system, pig farm are mandatory for setting stop bar before pig farm entrance and maintaining the records of inlet and outlet to and from pig farm. Also, the first step to the pig farm biosecurity is the control of entrance human, vehicles, animals and the related records including entrance and sterilization. In this study, the pig farm entrance control system using RFID technology and web-server system was developed. For human entrance, contact type RFID reading system(13.56MHz) was developed. And the 900MHz RFID system was used to detect vehicle entrance. The test result shows that system actuating, recognition, saving records to the web server was successful. Then, the full system of human entrance recording unit, vehicle entrance recording unit, entrance control system, human sterilizing booth containing a tablet for inputting visitor's record and sterilization record was tested. The records were wrote to web server DB through the data management web-program. Performance test shows the entrance control and data management in server was successfully operated. 정부의 축산업 및 축산차량 등록제 실시로 인하여, 양돈농가에서는 의무적으로 출입구에 차단장치를 설치하여야 하며 출입기록을 관리하여야 한다. 또한, 양돈장의 생물보안을 위해서도 출입인원과 차량, 동물 등의 양돈장 출입과 소독기록 등을 관리하여야한다. 본 연구에서는, RFID와 웹서버 시스템을 이용한 양돈장 출입차단 및 기록장치를 개발하였다. 사람의 출입관리를 위하여 13.56MHz의 접촉식 RFID 시스템을 개발하였으며, 차량 출입관리를 위해서는 900MHz RFID 시스템을 이용한 차량인식 시스템을 개발하였다. 시험결과 시스템 작동, 인식, 웹서버 데이터 저장 등의 성능이 양호한 것으로 판단되었다. 이후, 차량 출입시스템과 사람 출입 및 소독기록장치를 연동하여 시험을 실시하였으며, 기록된 데이터는 전용 프로그램을 이용하여 웹서버의 DB에 저장하였다. 성능시험결과, 출입관리와 데이터관리에 문제가 없는 것으로 판단되었다.